On the Functional Equation $\boldsymbol{U}_{\boldsymbol{t}}\boldsymbol{+} \boldsymbol{U}_{\boldsymbol{-t}} = \boldsymbol{V}_{\boldsymbol{t}} \boldsymbol{+} \boldsymbol{V}_{\boldsymbol{-t}}$ in a Banach Space - Pjanić, Karmelita (Sarajevo Journal of Mathematics, 2024)
In this paper we consider commuting one-parameter groups, $\{U_{t} : t \in R\}$ and $\{V_{t} : t\in R\}$ of unitary operators and the functional equation $U_{t} + U_{-t} = V_{t} + V_{-t}$ on a reflexive strictly convex Banach space with Gateaux differentiable norm. 2000 Mathematics Subject Classification. 47D03